Brickell, Katherine; Fernández, Melissa y Vasudevan, Alexander (eds.) (2017). Geographies of Forced Eviction: Dispossession, Violence, Insecurity - Solana Solana, Miguel (Documents d’Anàlisi Geogràfica, 2019)
Brickell, Katherine; Fernández, Melissa y Vasudevan, Alexander (eds.) (2017) Geographies of Forced Eviction: Dispossession, Violence, Insecurity Londres: Palgrave Macmillan, 244 p. ISBN 978-113751126-3